2006
DOI: 10.1039/b603268k
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of dissociation pressure upon doping level of Ti-doped sodium alanate—a possibility for “thermodynamic tailoring” of the system

Abstract: Pressure-concentration isotherms have been recorded for NaAlH(4) with different doping levels of titanium. It is well known that titanium accelerates the hydrogenation and dehydrogenation reactions in this system. Our studies have shown that the titanium doping also significantly alters the thermodynamics of the system, which is demonstrated by the change of the dissociation pressure with doping level. This can be explained by changes in the systems energy by dilution of the TiAl-alloy present after doping: Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 29 publications
4
38
0
1
Order By: Relevance
“…[57] It was recently shown that the dopant also alters the thermodynamics of the system. [58] This was determined by the change of the equilibrium pressure of titanium-doped NaAlH 4 depending on the doping concentration (Figure 8). During the dehydrogenation reaction, the highly concentrated TiAl 3 alloy produced in the doping reaction, is diluted with the generated aluminum.…”
Section: Complex Hydridesmentioning
confidence: 99%
“…[57] It was recently shown that the dopant also alters the thermodynamics of the system. [58] This was determined by the change of the equilibrium pressure of titanium-doped NaAlH 4 depending on the doping concentration (Figure 8). During the dehydrogenation reaction, the highly concentrated TiAl 3 alloy produced in the doping reaction, is diluted with the generated aluminum.…”
Section: Complex Hydridesmentioning
confidence: 99%
“…The PCI of the composites exhibits a broad distribution of thermodynamic properties whereas for bulk NaAlH 4 (catalysed either with TiCl 3 or CeCl 3 ) two distinct plateaus are observed, representing the two reaction steps of NaAlH 4 [see Figure 3 and reaction (1)]. The absorption and desorption branches of the PCI show small hysteresis (which is also observed for bulk catalysed NaAlH 4 at temperatures below the melting point [28] ). As can be seen in Figure 4, the PCI of samples 1 and 2 are almost identical (with the hydrogen content normalised to the maximum observed capacity).…”
mentioning
confidence: 92%
“…Neutral sodium and hydrogen vacancies are not stable neither in the bulk nor on the surface. Our studies explain why high oxidation states of Ti are crucial for its catalytic activity and point out that charge transfer effects are important in description of Ti in NaAlH 4 .…”
Section: Introductionmentioning
confidence: 69%
“…These materials posses, at present thermodynamic and kinetic limitations to prohibit them from practical applications. However, for almost 10 years it is known that addition of Ti-based catalysts significantly improves the kinetics of the hydrogen release and uptake [3] and affects the thermodynamic stability [4] of sodium alanate (NaAlH 4 ). Even though that NaAlH 4 does not fulfill DOE's storage requirements it is the most comprehensively studied system of all alanates and it serves as a model system for complex hydrides.…”
Section: Introductionmentioning
confidence: 99%